2019
DOI: 10.1002/hrm.21960
|View full text |Cite
|
Sign up to set email alerts
|

Is coworker feedback more important than supervisor feedback for increasing innovative behavior?

Abstract: A growing body of research explores human resource management practices that encourage employees to innovate. In this study, we examine the links between different sources of feedback (supervisor and coworker) and employees’ innovative behavior. Drawing on social exchange theory and the job demands‐resources theory, we first propose that work engagement and psychological contract breach mediate the relationship between supervisor feedback and employees’ innovative behavior. Second, we propose a moderated media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
59
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 117 publications
(206 reference statements)
10
59
0
4
Order By: Relevance
“…Management support has a small to medium effect size towards organisational commitment, which corroborate the finding by Eisenberger et al (1986) that higher management will have higher impact compared with lower management. Co-workers support has a small effect size but higher than supervisor support; this finding is in a similar vein with the research finding by Eva, Meacham, Newman, Schwarz, and Tham (2019) that co-workers can be used to supplement the lack of supervisor when required. Due to the offshore environment, employees tend to share their concerns or issues with peers instead of supervisors.…”
Section: Discussionsupporting
confidence: 85%
“…Management support has a small to medium effect size towards organisational commitment, which corroborate the finding by Eisenberger et al (1986) that higher management will have higher impact compared with lower management. Co-workers support has a small effect size but higher than supervisor support; this finding is in a similar vein with the research finding by Eva, Meacham, Newman, Schwarz, and Tham (2019) that co-workers can be used to supplement the lack of supervisor when required. Due to the offshore environment, employees tend to share their concerns or issues with peers instead of supervisors.…”
Section: Discussionsupporting
confidence: 85%
“…Some theorists also suggest that knowledge sharing is also dependent upon the varying abilities and motives of its recipients as IWBs rarely emerge in isolation and social contexts are critical (Kim et al, 2015). Although coworker feedback is known to enhance employee IWB (Christensen et al, 2015;Eva et al, 2019), we still know relatively little about how coworkers affect employee's IWB. Thriving is an individual factor which is self-regulatory in nature, helping employees to develop in a more positive direction at a personal level (Spreitzer et al, 2012).…”
Section: Palabras Clavementioning
confidence: 99%
“…Previous studies regarding leaders' feedback have often investigated its relation with business performance, job satisfaction, and organizational commitment [17,[22][23][24][25][26][27]. For example, Zhou [28] found that leader feedback positively related to members' personal creativity, but, with a few exceptions, there were limitations in showing the relationship to individual innovative behavior and the change process behind such behaviors [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%